2013
DOI: 10.1007/s11999-013-2955-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Early Functional Outcome Predict 1-year Mortality in Elderly Patients With Hip Fracture?

Abstract: Functional level at discharge is the main determinant of long-term mortality in patients with hip fracture. Motor FIM score at discharge is a reliable predictor of mortality and can be recommended for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 36 publications
5
51
2
1
Order By: Relevance
“…The results of many studies have confirmed the association between the combination of depressive symptoms and delirium and poor outcomes in older medical inpatients, 2,8,9,25 although the results of the current study are difficult to compare with those of other investigations because of the specific outcomes measured, differences in the follow-up period, and differences in the study population. The results of many studies have confirmed the association between the combination of depressive symptoms and delirium and poor outcomes in older medical inpatients, 2,8,9,25 although the results of the current study are difficult to compare with those of other investigations because of the specific outcomes measured, differences in the follow-up period, and differences in the study population.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The results of many studies have confirmed the association between the combination of depressive symptoms and delirium and poor outcomes in older medical inpatients, 2,8,9,25 although the results of the current study are difficult to compare with those of other investigations because of the specific outcomes measured, differences in the follow-up period, and differences in the study population. The results of many studies have confirmed the association between the combination of depressive symptoms and delirium and poor outcomes in older medical inpatients, 2,8,9,25 although the results of the current study are difficult to compare with those of other investigations because of the specific outcomes measured, differences in the follow-up period, and differences in the study population.…”
Section: Discussionmentioning
confidence: 50%
“…The cognitive status of all participants without delirium who entered the study was assessed using the 10-item Short Portable Mental Status Questionnaire (SPMSQ) 9 during baseline interviews. The covariates measured included sociodemographic characteristics (age, sex, education level), cognitive status, physical status, medical comorbidities, vision impairment, and number of drugs used.…”
Section: Sociodemographic Characteristics Mental Status Physical Stmentioning
confidence: 99%
“…Prefracture functional level was assessed by the motor subscale of the Functional Independence Measure (motor FIM) . The FIM score has been used in different prospective and retrospective cohort studies in patients with hip fracture, and its reliability has been observed directly with both patient and proxy responses . The motor FIM scale rates a patient's independence in self‐care, sphincter control, transfer, and locomotion.…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive level at admission was assessed with the Short Portable Mental Level Questionnaire. 7 Based on the number of correct answers, the 10-item questionnaire classifies a patient's cognitive level as lucid (8)(9)(10), mild-tomoderate cognitive dysfunction (3)(4)(5)(6)(7), and severe cognitive dysfunction (0-2). In patients with a Short Portable Mental Level Questionnaire score less than 3, all observed variables, except for cognitive level, were collected from a proxy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation